2012
DOI: 10.1017/s0031182012000029
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in infants and pre-school-aged children in sub-Saharan Africa: implication for control

Abstract: Until recently, the epidemiology and control of schistosomiasis in sub-Saharan Africa have focused primarily on infections in school-aged children and to a lesser extent on adults. Now there is growing evidence and reports of infection in infants and pre-school-aged children (≤ 6 years old) in Ghana, Kenya, Mali, Niger, Nigeria and Uganda, with reported prevalence from 14% to 86%. In this review, we provide available information on the epidemiology, transmission and control of schistosomiasis in this age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 48 publications
10
68
0
Order By: Relevance
“…19,28 Wearing shoes was associated with less schistosomiasis in this study. Alemu et al reported similar results.…”
Section: Discussionsupporting
confidence: 48%
“…19,28 Wearing shoes was associated with less schistosomiasis in this study. Alemu et al reported similar results.…”
Section: Discussionsupporting
confidence: 48%
“…These children, who are infected by the parasite, are a source of continuous reinfestation for the community and are therefore those who are likely to benefit the most from the program. 18,20,21 It is difficult to determine the extent to which the treatment is effective in controlling the disease, and what the impact of the currently ongoing health education campaigns and construction of latrines program really is. It is therefore necessary to continue running health and hygiene programs for the village inhabitants because the role of sanitation and hygiene is crucial to interrupt Schistosoma life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]28,29 It has also been discussed whether preventive chemotherapy should be extended from schoolaged to pre-school-aged children. 27,[30][31][32] However, there are a number of issues that must be addressed before policy recommendations can be made regarding the inclusion of preschoolers in preventive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%